Aggregate wage flexibility in selected new EU member states - Ian Babetskii (Center for Economic Studies and ifo Institute (CESifo), 2007)
A fixed exchange rate regime eliminates one degree of freedom in absorbing macroeconomic shocks. Therefore, there is a call for higher labor market flexibility in countries which are members of the monetary union or those which intend to join the monetary union. Focusing on the cross-country analysis of labor markets in the enlarged European Union over 1995- 2004, this paper aims to assess empirically the role of aggregate wages as a correction mechanism for dealing with economic disturbances. We apply classical time series/panel, Bayesian, and cointegration techniques to determine the extent to which aggregate wages can accommodate shocks in the economy.
Keywords: E24; E52; C22; C33; P20; 330; Arbeitsmarktflexibilisierung; Lohnrigidität; Europäischer Währungsverbund; Kointegration; Schätzung